Food-For-All: A Food Donation Management System - Jalaluddin, Nur Syazleen; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2025)
Food insecurity and hunger are major issues in Malaysia, especially for the B40 community who often struggle to get enough food. These problems also worsen during disasters like floods or pandemics, which disrupt food supply chains. NGOs help by collecting and distributing food, but they face difficulties such as managing overstock and shortages, tracking expiration dates manually, and recording donor information using paper forms. To solve these problems, the “Food-For-All: A Food Donation Management System” was developed. This system offers a mobile-view web platform for donors and a web-based platform for NGOs. It was built using the Waterfall model and tested through both alpha and beta testing phases. It is expected to allow donor view the items needed, submit online donation forms, and can view the updates when their donations are distributed. The system also automates the monitoring of expiration dates and creates reports for each donation program.